Socio-Demographic Profile of HIV Positive Patients of Mucocutaneous Manifestation Attending Skin & VD Department of Government Medical College, Surat - Yogesh Patel; Dipak Umarigar; Bipin Vasava; Nipul Vara; Nikita Patel (Medsci Publications, 2013)
Introduction: AIDS, the acquired immuno-deficiency syndrome is a fatal illness caused by a retrovirus known as human immuno-deficiency virus which break down the body's immune system, leaving the victim vulnerable to a host of of life threatening opportunistic infections, neurological disorders or unusual malignancies. Objectives: The objectives of the study were to study socio demographic profile of HIV positive patients and to find out the possible high risk behaviour of having HIV. Methodology: It is a cross sectional study conducted at Skin & VD department of Government Medical College, Surat. After taking informed consent, a semi structured and pre-tested proforma was used to collect all the quantitative information related to possible mode of transmission of HIV and history of risk factors in the spouse and parents in case of children, from the all HIV positive patients attending OPD who full fill the inclusion criteria of the study. Results: The present study included 100 HIV positive patients attending OPD during June 2004 to December 2005. 94 % patients were among the sexually active group 15-49 years comparable with 89% of NACO report. In present study there were 76% male and 24% female compared to 70.82% & 29.17% respectively in NACO report. 69% patients married, 12% unmarried,4% divorced 10% were widow and 5% children in this study.53% patients were either illiterate or primary education. Conclusion: Until a vaccine or cure for AIDS is found, the only means at present available is health education to enable people to make life saving choices avoiding multiple sexual relation and use condom.